2003
DOI: 10.1002/ajmg.a.20410
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma, pinealoma, and mild overgrowth in a boy with a deletion of RB1 and neighbor genes on chromosome 13q14

Abstract: We report on a 10-year-old boy with a normal karyotype and a chromosome 13q14 deletion of the retinoblastoma gene (RB1) by fluorescence in situ hybridization (FISH). He showed subtle signs of overgrowth, including macrocephaly, hepatomegaly, and inguinal hernia. The boy also had cryptorchism and mild developmental delay. In his first months of life, variant Wiedemann-Beckwith syndrome was tentatively suspected and he was included in a careful tumor prevention program. At the age of 11 months, bifocal retinobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…31 Of note, all deletions found in our cohort are centromeric to 13q33.3q34, a region that was reported to be critical for microcephaly by Kirchhoff et al 30 Interestingly, a few patients in this cohort and in previous reports showed macrocephaly. 8,9 However, the pattern of deleted regions was the same as that in patients with normocephaly. Of note, the MTLR1/ MLNR gene, which encodes for the growth hormone secretagogue receptor found in the pituitary gland and brain, is involved in the control of growth hormone release, 32 and is deleted in 5/6 patients with macrocephaly in our cohort.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…31 Of note, all deletions found in our cohort are centromeric to 13q33.3q34, a region that was reported to be critical for microcephaly by Kirchhoff et al 30 Interestingly, a few patients in this cohort and in previous reports showed macrocephaly. 8,9 However, the pattern of deleted regions was the same as that in patients with normocephaly. Of note, the MTLR1/ MLNR gene, which encodes for the growth hormone secretagogue receptor found in the pituitary gland and brain, is involved in the control of growth hormone release, 32 and is deleted in 5/6 patients with macrocephaly in our cohort.…”
Section: Discussionmentioning
confidence: 66%
“…Additional case reports on patients with an interstitial 13q deletion involving band 13q14, describe macrocephaly, hypertelorism, proptosis, cleft palate, macroglossia, hypotonia and mild to severe developmental delay. [8][9][10] In two patients with Rb and an interstitial deletion extending to 13q22, Hirschsprung disease was reported. 11,12 All these patients were analyzed using standard cytogenetic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Disagreement was resolved by consensus. The parameters evaluated on MR imaging were selected on the basis of literature study 4,7,[12][13][14][15][16][17][18][19][20][21][22][23][24] and were divided into the following categories: benign or malignant tumor (tumor of the pineal gland, pineal cyst, or other); structural anomalies (corpus callosum agenesis, holoprosencephaly, encephalocele, Dandy-Walker malformation or a variant, hypoplasia of the basic pontis, microcephaly and polymicrogyria, or other); and degree of myelinization, ventriculomegaly, or coincidental findings. Special attention was paid to myelinization to clarify possible cognitive symptoms.…”
Section: Image Analysismentioning
confidence: 99%
“…Only in case reports, describing patients with 13q deletion syndrome or in combination with retinoblastoma, are congenital brain abnormalities or brain disorders indicative of cognitive symptoms reported. 4,7,[12][13][14][15][16][17][18][19][20][21][22][23][24] Ballarati et al 25 reported central nervous system anomalies such as DandyWalker malformation, cerebellar hypoplasia, cortical dysplasia, and agenesis of the corpus callosum in patients with 13q deletion. Although one can assume that these symptoms are due to 13q deletion syndrome, it is interesting to evaluate whether (structural) brain abnormalities are involved in patients with retinoblastoma.…”
mentioning
confidence: 99%
“…Afterward, a patient with a X:13 translocation and phenotypic features peculiar to the 13q14 deletion syndrome was described (Dries et al 2003). Finally, in 2004, a patient with retinoblastoma, pinealoma and mild multiple congenital anomalies/mental retardation syndrome (MCA/MR) and a germline 13q14 deletion were reported (Skrypnyk and Bartsch 2004).…”
Section: Introductionmentioning
confidence: 99%